2016
DOI: 10.1016/j.jcte.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

High dose vitamin D administration in ventilated intensive care unit patients: A pilot double blind randomized controlled trial

Abstract: Background There is a high prevalence of vitamin D deficiency in the critically ill patient population. Several intensive care unit studies have demonstrated an association between vitamin D deficiency [25-hydroxyvitamin D (25(OH)D) < 20 ng/mL] and increased hospital length of stay (LOS), readmission rate, sepsis and mortality. Material and Methods Pilot, double blind randomized control trial conducted on mechanically ventilated adult ICU patients. Subjects were administered either placebo, 50,000 IU vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
220
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(229 citation statements)
references
References 43 publications
4
220
1
4
Order By: Relevance
“…Indeed, Vitamin D3 has been shown to directly regulate expression of the human antimicrobial peptides LL-37 and hBD-2 (179, 180). However, a recent pilot study in mechanically ventilated ICU patients showed that high dose of vitamin D3 was associated with decreased hospital length of stay, but no statically significant change in plasma LL-37 concentrations or other clinical outcomes (181). While the stimulatory effect of Vitamin D has been described for the osteogenic potential of MSCs (182), future experiments are required to address their effect on the expression of AMPs both in vitro and in vivo .…”
Section: Trends Future Perspectives and Challengesmentioning
confidence: 99%
“…Indeed, Vitamin D3 has been shown to directly regulate expression of the human antimicrobial peptides LL-37 and hBD-2 (179, 180). However, a recent pilot study in mechanically ventilated ICU patients showed that high dose of vitamin D3 was associated with decreased hospital length of stay, but no statically significant change in plasma LL-37 concentrations or other clinical outcomes (181). While the stimulatory effect of Vitamin D has been described for the osteogenic potential of MSCs (182), future experiments are required to address their effect on the expression of AMPs both in vitro and in vivo .…”
Section: Trends Future Perspectives and Challengesmentioning
confidence: 99%
“…The parent RCT was approved by the Emory University Institutional Review Board (www.clinicaltrials.gov NCT01372995) and published previously (5). Written informed consent was obtained from all subjects or their legally authorized representative.…”
Section: Methodsmentioning
confidence: 99%
“…those with frank vitamin D deficiency) without improvement in other clinical outcomes; thus, vitamin D therapy in this setting remains controversial and there is a need for further investigations (15, 38). In our recent RCT in mechanically ventilated adults, high-dose vitamin D 3 increased plasma total 25(OH)D levels by 2 to 3-fold, but did not alter plasma LL-37 concentrations (5). …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations